STRATEGI PENGEMBANGAN KOMPETENSI MANAJERIAL TEKNIS YUDISIAL KEPANITERAAN PENGADILAN - Cuhandi (Jurnal Governansi, 2026)
The role of the clerkship helps the smooth running of the trial process. Therefore, competency development in the clerkship field needs to be carried out to realize a supreme judicial body. The purpose of this study is to determine and analyze the suitability of training materials and training model development strategies provided to court clerks, which are organized by the Center for Education and Training of Management and Leadership of the Supreme Court of the Republic of Indonesia in order to improve managerial competencies including aspects of conceptual skills, human relations skills, and technical skills. The type of research is qualitative research with a case study approach. Data collection techniques use questionnaires, interviews, and documentation. The technique for determining sources uses purposive sampling. Data validation techniques use triangulation of data sources and methods. Data analysis techniques use interactive analysis consisting of data reduction, data display, and conclusion drawing/verification. The results of this study conclude that: (1) The training materials provided in the court clerkship training organized by the Center for Education and Training of Management and Leadership of the Supreme Court of the Republic of Indonesia in order to improve managerial competencies are not yet appropriate for the position of clerk, which is a middle-level leadership position (middle management); (2) The human resource development strategy for the Court Clerkship is implemented through managerial competency training to improve conceptual, human, and technical skills related to the core duties and functions of the unit, in accordance with the position level held.